A cross-cultural interpersonal model of adolescent depression: A qualitative study in rural Nepal. (February 2021) - Rose-Clarke, Kelly; Hassan, Eliz; BK, Prakash; Magar, Jananee; Devakumar, Delan; Luitel, Nagendra P.; Verdeli, Helen; Kohrt, Brandon A.
Abstract: Most cross-cultural qualitative research on depression has been descriptive, documenting symptoms and explanatory models. There is a lack of qualitative research testing theoretical models of depression. The interpersonal model conceptualises grief, interpersonal disputes, role transitions and social isolation as the context in which depression develops and is the basis of interpersonal therapy (IPT), which is increasingly used in cross-cultural settings to treat depression. We aimed to qualitatively evaluate to what extent the interpersonal model can explain adolescent depression in Nepal. Data were collected between December 2018 and April 2019 and comprised transcripts from 126 participants: 25 semi-structured interviews with depressed adolescents aged 13–18; four focus group discussions with adolescents (N = 38), four with parents/caregivers (N = 39), and two with teachers (N = 17); and seven semi-structured interviews with health and non-governmental organisation workers. We coded data using an analytical framework comprising deductive codes representing key concepts from the interpersonal model of depression and IPT, including principles, techniques and strategies. Participants mainly related depression to interpersonal problem areas of grief, dispute, role transition and social isolation. Interpersonal disputes were common, and for many adolescents this involved parental physical and emotional abuse. Although role transitions were common few adolescents grieved loss of the prior role. Distress related to social isolation was evident despite close physical proximity and extensive social interaction with family and community members. Adolescents described coping strategies that were similar to strategies central to IPT, e.g. identifying helpful and unhelpful relationships and generating options and ways of managing problems. In conclusion, interpersonal problems are relevant to this population and conceptualisations align with core principles of the interpersonal model of depression. The findings highlight the importance of addressing abuse and maltreatment in depression aetiology. They also inform future cultural adaptations of IPT in Nepal and beyond, including the opportunity to integrate local coping strategies. Highlights: Testing psychological models cross-culturally is important for adapting therapies. Interpersonal problems trigger depression among adolescents in Nepal. Experiences of depression align with core principles of interpersonal therapy (IPT). Few adolescents use IPT strategies to address interpersonal problems. Models of depression must incorporate poverty, migration and abuse as risk factors.